REVIEW OF PERCEPTION USEFULNESS AND EASE OF USE PERCEPTION OF INTENTION TO USING THE BRI MOBILE APPLICATION FOR SMALL BUSINESS LOAN ENTREPRENEURS IN SERANG CITY - Hamdan (International Journal of Economics and Management Research, 2022)
Study aims to determine the effect of perceived usefulness and perceived ease of use on intentions to use the BRI mobile application. The research method used is a quantitative method which views human behavior or behavior as predictable, objective and measurable, and aims to test certain theories by examining the relationship between between variables. The research data was obtained from questionnaires distributed to respondents, namely Bank Rakyat Indonesia customers who use the BRI mobile application, totaling 120 respondents. Based on the results of data processing indicated by the t-count value, it was found that the variables X1 (perceived usefulness) and X2 (perceived ease of use) had a significant influence on the intention to use (Y) the BRI mobile application. The results of the F test also show that perceived usefulness and perceived ease of use have a simultaneous (simultaneous) effect on customers' intention to use the BRI mobile application.